African writing in English in Southern Africa : an interpretation of the contribution to world literature of Black Africans within the confines of the Republic of South Africa, Rhodesia and the former British protectorates in Southern Africa - Barnett, Ursula A (Department of English Language and Literature, 2016)
Includes bibiographical references (pages 236-271).